The theoretical and applied principles of the investigation of suicide prevention in penitentiary institutions of Ukraine - Bogatyrev, Ivan G.; Terekhova, Lyubov V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Suicide prevention in penal establishments and pre-trial institutions is the one of priority tasks of State Penitentiary Service of Ukraine. This problem could be solved only after serious analysis of current situation in wide social context. The actual questions of research for the reasons of suicides as well as increase of their number in prisons are illuminated in the article. The methods of suicide preventing among convicted persons and inmates are proposed.